Pengaruh Tayangan Berita Kriminal Televisi terhadap Perilaku Remaja Desa Senaung Kabupaten Muaro Jambi - Suryadi; Agus Slamet Nugroho; Mila Wahyuni; Usrial (MAUIZOH: Jurnal Ilmu Dakwah dan Komunikasi, 2019)
This study limits the discussion related to criminal news on the Surya Citra Televisi (SCTV) television station. The purpose of this study was to determine the attitude changes that occur in adolescents after watching criminal news shows, to find out the motivation of teenagers to watch crime news shows on television (SCTV), and to find out the efforts of teenagers to overcome the negative impact of crime news broadcasts on television (SCTV) both independently and independently. or with the help of other parties. Data collection for this research was conducted through interviews and observations. The study found that crime news broadcasts have influenced the behavior of teenagers in Senaung Village, but this influence is not always a negative impact nor a positive impact. The influence of crime news shows on adolescent behavior is very dependent on the personality of the teenager. Adolescent personality is also shaped by family, environment, and peer themes.